The Fabaceae in Northeastern Mexico (Subfamily Papilionoideae, Tribes Amorpheae, Brongniartieae, and Dalbergieae) - Eduardo Estrada Castillón; José Ángel Villarreal Quintanilla; Juan Antonio Encina Domínguez; Arturo Mora Olivo; Jaime Sánchez Salas; Gisela Muro Pérez; Eduardo Alanís Rodríguez; Renata Aidé Valdés Alameda; Nelly Sandoval Mata; Gilberto Ocampo (Plants, 2025)
A compendium of the legumes of the subfamily Papilionoideae, tribes Amorpheae, Brongniarteae, and Dalbergieae in northeastern Mexico is presented for the first time, including changes in their botanical nomenclature within tribes and genera. Based on recently published studies, the taxonomic limits of several genera and new ones segregated such as Marina and Ctenodon are clarified and included. Based mainly on fieldwork over the past 40 years, as well as reviewing specimens in national and international herbaria, we show the total diversity of legumes of the subfamily Papilionoideae, tribes Amorpheae, Brongniarteae, and Dalbergieae. The three tribes include 16 genera and 75 species. Tribe Amorpheae comprises five genera (Amorpha, Dalea, Eysenhardtia, Marina, and Psorothamnus) and forty-three species; tribe Brongniartieae comprises two genera Brongniartia and Harpalyce) and eight species; and tribe Dalbergieae comprises nine genera (Aeschynomene, Amicia, Arachis, Ctneodon, Dalbergia, Diphysa, Nissolia, Stylosanthes, and Zornia) and twenty-four species. Dalea is by far the genus with the highest number of species and infraspecific categories, as well as in a number of endemisms because 17 (51%) of them are endemic to Mexico, and six of them are endemic to the northeastern part of the country. Of the 13 species of Eysenhardtia present in Mexico, 31% of them reach the northeast region and three of them are exclusive to this region. There are no species of the Brongniartieae and Dalbergieae tribes endemic to northeastern Mexico, but 10 of their species are endemic to Mexico.